Factors affecting student’s perceived-usefulness of social media in collaborative learning / Ameer Shahreen Samsol Azaman - Samsol Azaman, Ameer Shahreen (Faculty of Business and Management, 2018)
This study revolves around social media where researcher want to understand factors that affecting student’s perceived-usefulness of social media in collaborative learning. Descriptive study is used where questionnaire distributed to 76 respondents which are chosen from students from UiTM Melaka Kampus Bandaraya that are taking subjects of Entrepreneurship which used method of simple random sampling with the help of Krejcie and Morgan table to determine the number of sample. The data collected is then analysed with Reliability test, Pearson Correlation Coefficient Statistics and Multiple Regression Analysis. This study’s objective are to determine is there relationship between independent variable towards perceived of social media usefulness and which of the factor have the most significant towards the dependent variable. The result of the study indicate that all of the independent variables (interactivity with peers, interactivity with teachers and engagement) has significant relationship towards perceived of social media usefulness. The factor that gives the highest impact is interaction with teachers that will influence the factors affecting student’s perceived-usefulness of social media in collaborative learning.